2016
DOI: 10.1002/art.39476
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an Association of TNFAIP3 Polymorphisms With Matrix Metalloproteinase Expression in Fibroblasts in an Integrative Study of Systemic Sclerosis–Associated Genetic and Environmental Factors

Abstract: Objectives Systemic Sclerosis (SSc) is a fibrotic disease attributed to both genetic susceptibility and environmental factors. Our studies tried to demonstrate how human fibroblasts with SSc associated genetic variants respond to time-course and dose-response expression of the extracellular matrix (ECM) genes with silica particle stimulation. Methods A total of 200 fibroblast strains were examined for ECM gene expression after stimulation by silica particles. The fibroblasts were genetically profiled with Im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 51 publications
0
17
0
2
Order By: Relevance
“…Qualitative and quantitative changes in the extracellular matrix (ECM) related to a disturbed balance between MMPs and tissue inhibitors of metalloproteinases (TIMPs) have been demonstrated to play a significant role in the pathophysiology of PH and SSc . In particular, the generation of fragments and the exposure of functionally important cryptic sites in collagens, laminins, elastin, or fibronectin are known to stimulate the production of matrix glycoproteins and release of growth factors that are encrypted in the ECM or from their cell membrane–bound precursors, and to facilitate pulmonary artery smooth muscle cell proliferation and contribute to their switch from a contractile to a migratory phenotype .…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative and quantitative changes in the extracellular matrix (ECM) related to a disturbed balance between MMPs and tissue inhibitors of metalloproteinases (TIMPs) have been demonstrated to play a significant role in the pathophysiology of PH and SSc . In particular, the generation of fragments and the exposure of functionally important cryptic sites in collagens, laminins, elastin, or fibronectin are known to stimulate the production of matrix glycoproteins and release of growth factors that are encrypted in the ECM or from their cell membrane–bound precursors, and to facilitate pulmonary artery smooth muscle cell proliferation and contribute to their switch from a contractile to a migratory phenotype .…”
Section: Discussionmentioning
confidence: 99%
“…One recent study investigated the interactions between genetic and environmental factors (silica particles) in SSc using a fibroblast model [61]. The authors reported that the SNP rs58905141 in TNFAIP3 was strongly and persistently associated with silica particles-stimulated MMP1 and MMP3 expression in fibroblasts, suggesting a potential interaction of the SSc susceptibility locus in TNFAIP3 and silica particles, which might be associated with the development of SSc through inflammatory mechanisms.…”
Section: Genetic Involvementmentioning
confidence: 99%
“…Out of the 19 genes that were previously identified as harboring SSc susceptibility SNPs in Whites, only TNFAIP3 was nominally significant in the gene-level analysis in African Americans. Previously, we showed that SNPs of TNFAIP3 had a strong association with expression of matrix metalloproteinase 1 and 3 in fibroblasts of ethnically diverse patients in response to silica particle stimulation [ 27 ].…”
Section: Discussionmentioning
confidence: 99%